Pioneer Species, Persistents And Germination Tests In Montane Forests Of Central Ridge, Colombia - Sierra Escobar, Jorge Alberto; Henao, Daniela Marin; Suaza, Daniela Salazar; Garcés, Mabel Vanessa García; Abril, Mario Alberto Quijano (Universidad Pedagógica y Tecnológica de Colombia, 2020)
High fragmentation and deterioration of the low montane humid forest makes its ecological restoration a priority, due to this, mechanisms that tend to recover the forest are required, especially in priority areas. This study aimed to provide tools that allow restorers to have information about native species with potential for restoration. For this purpose, a 500-hectare low montane humid forest was selected, which was divided into three zones according to its anthropic intervention. In each area physicochemical analyzes of soils and floristic inventories were carried out analyzed with different indexes of diversity and vegetation profiles. In addition, tree and shrub species were classified as pioneer and persistent. Finally, fruits and seeds of the species that were fructified at the time of sampling were collected and analyzed, carrying out germination tests in each of them. The results suggest that in general the zones presented high diversity (Shannon index) with values ​​between 2.804 and 3.414. Species with the highest IVI were Miconia resima, Palicourea angustifolia, Palicourea garciae, Cavendishia pubescens, and Clusia multiflora. The largest number of fruiting species was found in areas 1 and 2 (intervened and moderately intervened), 40% of the seeds extracted germinated, finally, 42 species were classified in the pioneer and persistent categories. In conclusion, the information obtained in this project is expected to serve in part as a support tool for the ecological restoration of the low montane humid forest.